The interplay between gender and major on content knowledge and self-beliefs in the English-medium instruction context: A comparative study between university students from Japan and South Korea. (July 2022) - Kim, Victoria; Thompson, Gene
Abstract: This article explores differences in content knowledge, English language proficiency, and motivation for learners studying via English medium instruction (EMI) at universities in Korea and Japan. It draws upon content knowledge test and questionnaire data from a total of 455 students from two institutions, representing three groups of students (business majors from the Japanese institution, business majors from the Korean institution, and non-business majors from the Korean institution). Results from a 3 × 2 factorial ANOVA indicated a significant interaction between the effect of student group and gender on content knowledge test scores and motivated behaviour, and significant differences between student groups on a range of motivational measures. Findings indicated differing learner profiles between the three groups: business-major students from the Korean institution tended to have stronger motivation and high content knowledge, regardless of gender while significant differences were identified between females and males within the Japanese business major group and non-business major group from the Korean institution. The comparative nature of the study highlights the potential impact of demographic variables across and between groups of EMI learners, indicating areas for future exploration within each of the programs explored in this study.